FORMATION OF ABILITIES ETHNO-CULTURAL ACTIVITY AT THE FUTURE TEACHERS OF HISTORY - Yanovskaya, Larysa G. (Educological discourse, 2016)
In the article the features of the formation of ethno-cultural skills activity at the future teachers of history by means of historical education is examined; the importance of ethnic and cultural activities in the lessons of history is described; purpose was defined, model of training of future history teachers to ethno-cultural activity is presented, the definition of the main components – the cognitive, procedural controlling.